(untitled) (Revista de Artes Marciales Asiáticas, 2018)
The aim of this study was to describe the basic functional profile (VAFB) of a group of 13 competitive judokas at the national level. The method used was the basic functional Assessment tests battery proposed by Gil-López (2018). The results obtained indicate a Global Injury Risk Index (LRTI) of 45.74 ± 2.01%. The most common compensations among all judokas were external rotation of the foot, right/left, left/right foot pronation, loss of lumbo-pelvic dissociation, chest movement, winged scapulae and cervical protation. As for the years of practice, there were differences in the shoulder joint test (SM), where there was a greater number of compensations in the judoka who had been practicing judo less than ten years. Participants did not show a high risk of injury, but it is recommended to include corrective exercises to improve the judokas’ detected deficits.